2022
DOI: 10.3390/atmos13020308
|View full text |Cite
|
Sign up to set email alerts
|

Airborne Fungal Spore Review, New Advances and Automatisation

Abstract: Fungal spores make up a significant portion of Primary Biological Aerosol Particles (PBAPs) with large quantities of such particles noted in the air. Fungal particles are of interest because of their potential to affect the health of both plants and humans. They are omnipresent in the atmosphere year-round, with concentrations varying due to meteorological parameters and location. Equally, differences between indoor and outdoor fungal spore concentrations and dispersal play an important role in occupational he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 152 publications
(280 reference statements)
1
28
0
Order By: Relevance
“…In the present work, the most abundant fungal genera detected in the analyzed sampling environments were Alternaria, Cladosporium and Penicillium. These fungal genera have been similarly identified as dominant taxa in various air environments analyzed in previous studies ( Fang et al, 2005 ; Aira et al, 2007 ; Ekmekci, 2008 ; Martinez-Bracero et al, 2022 ). For instance, Cladosporium , Penicillium , Aspergillus , and Alternaria were identified as the most abundant fungal genera in the outdoor environments of Manisa, Turkey ( Ekmekci, 2008 ).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In the present work, the most abundant fungal genera detected in the analyzed sampling environments were Alternaria, Cladosporium and Penicillium. These fungal genera have been similarly identified as dominant taxa in various air environments analyzed in previous studies ( Fang et al, 2005 ; Aira et al, 2007 ; Ekmekci, 2008 ; Martinez-Bracero et al, 2022 ). For instance, Cladosporium , Penicillium , Aspergillus , and Alternaria were identified as the most abundant fungal genera in the outdoor environments of Manisa, Turkey ( Ekmekci, 2008 ).…”
Section: Discussionsupporting
confidence: 63%
“…The concentration of airborne fungi in different environments varies depending on a number of factors, including fungal substrates availability and human activity Miller, 1992 ; Sorenson, 1999 ; Kurup et al, 2000 ; Adhikari et al, 2004 ). Airborne fungi are considered to be linked to air pollution and implicated in negative health consequences on humans, animals, and plants ( Bush and Portnoy, 2001 ; Shelton et al, 2002 ; Martinez-Bracero et al, 2022 ). Approximately, 150 allergenic fungal taxa have been identified to date ( Simon-Nobbe et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among these, fungal spores constitute an important component of "primary biological aerosol particles (PBAPs)" and are present for significant periods of the year in a variety of biogeographic areas. Major sources of PBAPs include farms, woods, green areas, and decaying plant matter (Martinez-Bracero, et al, 2022;Grinn-Gofro' n, et al, 2018). Most fungal spores are discharged mainly through the air, where they will hang out for a while before traveling across short or long distances.…”
Section: Airborne Fungal Sporesmentioning
confidence: 99%
“…Irish famine is the typical example of their survival and occurence, which was caused by Phytophthora infestans (potato blight). During storage of agri-produce, many common molds such as Alternaria, Aspergillus, Cladosporium, and Penicillium were demonstrated to contaminate the food (Martinez-Bracero, et al, 2022). This review emphasizes about the latest findings on spatial variation of airborne fungal and fungus-like spores on the basis of different sampling techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The respiratory tract is continuously exposed to fungal spores in our environments, and studies have shown a high proportion of fungi in nasal mucus and bronchial sputum cultures, even in healthy subjects [5,6]. Aspergillus is the main indoor fungus in humid environments [7][8][9], the most common fungus causing fungal sinusitis and fungal allergic rhinitis [10,11], and the most common type of fungus secreted from sinonasal aspirate in CRS patients [12]. The incidence of fungal rhinosinusitis occurs most commonly in the maxillary sinus, followed by the sphenoid sinus, ethmoid sinus, and frontal sinus.…”
Section: Introductionmentioning
confidence: 99%